Pengaruh Electronic Word of Mouth, Kualitas Produk, dan Brand Image Terhadap Keputusan Pembelian Online Shop (Studi Kasus Pada Mahasiswa Generasi Z UNISMA) - Tanari, Vika; Priyono, Achmad Agus; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of Electronic Word of Mouth, Product Quality, and Brand Image on online shopping purchase decisions among UNISMA Generation Z students.  The population of this study is the UNISMA Generation Z who are over 18 years old and have made online purchases in the marketplace.  Meanwhile, the sample used consisted of 85 samples.  SPSS 16 for Windows data analysis.  The research results show that 1) electronic word of mouth has a positive and significant influence on online shop purchase decisions.  2) Product quality has a positive and significant influence on online shop purchase decisions.  3) Brand Image has a positive and significant influence on online shop purchase decisions. Keywords: E-WoM, Product Quality, Brand Image and Purchase Decision.